Comparative Quantitative Study of Ardisiacrispin A in Extracts from Ardisia crenata Sims Varieties and Their Cytotoxic Activities. Issue 7 (4th June 2021) - Podolak, Irma; Żuromska‐Witek, Barbara; Grabowska, Karolina; Żebrowska, Sara; Galanty, Agnieszka; Hubicka, Urszula
Abstract: Ardisia crenata Sims (Primulaceae) occurs in natural habitats in two varieties, bearing red or white fruits. While roots of the red‐berried ardisia are valued as a medicinal product, the pharmacological activity of which is attributed to triterpene saponins, including ardisiacrispin A, data on the white‐berried variety are scarce. A TLC‐densitometric method was developed and validated to estimate the levels of saponins, calculated as ardisiacrispin A, in different plant parts in both varieties. Their content amounted to 22.17±4.75 and 25.72±1.46 mg/g d.w. in roots, and 2.64±0.74 and 3.43±0.70 mg/g d.w. in fruits of red‐berried and white‐berried ardisia, respectively. Assessment of cytotoxicity of ardisiacrispin A and A. crenata extracts on a panel of human cancer cell lines revealed a similar effect of root extracts from both varieties, with the highest potency against melanoma WM793 and colon cancer Caco2. Thus, roots of the white‐berried variety may be treated as a substitute for red‐berried ardisia and serve as an alternative source for the acquisition of plant material rich in bioactive saponins. Abstract :